A Test-Items Analysis of English Teacher-Made Test - Muslim Darmawan; Sudarsono -; Dwi Riyanti; Yohanes Gatot Sutapa Yuliana; Sumarni (Journal of English Education and Teaching, 2022)
The primary purpose of this study is to find out information about the quality of item analysis on English teacher-made tests related to the difficulty level, item discrimination level, validity, and reliability of the final semester assessment for the twelfth-grade student of SMAN 8 Pontianak in the academic year 2020/2021. The researcher conducted this study using descriptive quantitative analysis with the data obtained from the English teacher-made test, consisting of 40 items with 257 test-takers of twelfth-grade students. The researcher analyzed the test items by using the combinations of Master TAP and SPSS Version 16 applications. Based on the difficulty level, the analysis results show that 22 items were categorized as easy, 14 items as medium, and four items as difficult level. Moreover, the item level of item discrimination shows that 9 items are categorized as poor, 18 items as enough, and 13 items as good index level. The analysis results also show that 23 items as valid questions, while the other 17 are invalid. On the other hand, the questions' reliability level showed satisfactory results, with the K-R20 result of 0.835. The results of the analysis showed that there were some questions that had already of good quality, but some problematic items were also found after being analyzed. Therefore, it is necessary for the teacher to conduct an evaluation of the problematic items so that the assessment process will be better in the future. The primary purpose of this study is to find out information about the quality of item analysis on English teacher-made tests related to the difficulty level, item discrimination level, validity, and reliability of the final semester assessment for the twelfth-grade student of SMAN 8 Pontianak in the academic year 2020/2021. The researcher conducted this study using descriptive quantitative analysis with the data obtained from the English teacher-made test, consisting of 40 items with 257 test-takers of twelfth-grade students. The researcher analyzed the test items by using the combinations of Master TAP and SPSS Version 16 applications. Based on the difficulty level, the analysis results show that 22 items were categorized as easy, 14 items as medium, and four items as difficult level. Moreover, the item level of item discrimination shows that 9 items are categorized as poor, 18 items as enough, and 13 items as good index level. The analysis results also show that 23 items as valid questions, while the other 17 are invalid. On the other hand, the questions' reliability level showed satisfactory results, with the K-R20 result of 0.835. The results of the analysis showed that there were some questions that had already of good quality, but some problematic items were also found after being analyzed. Therefore, it is necessary for the teacher to conduct an evaluation of the problematic items so that the assessment process will be better in the future.